Effect Of Incubation Temperature On Ikta's Quail Breed With New Rolling Mechanism System / Mohd Badli Ramli...[et al.] - Ramli, Mohd Badli; Wahab, M.S; Zain, B.A; Raus, A.A; Kamarudin, K.; Sa`ude, N; Haq, R; M, Ibrahim; Ahmed, Aqeel (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Successful of hatching rates in incubation quails IKTA(Institut Kemahiran Ternakan Ayam) may differ between each hatchery. There is numerous factor that influence embryonic development, among the parameter is temperature, humidity, air movement, eggs placement etc., This factor may lead to high percentage of embryo hatching and healthy DOQ (day one quail). Nine incubations were performed with 3 set of different temperature to examine the effect of different setting temperature. For eggs placement, eggs were turns using rolling mechanism 360° for every hour. Eggs obtained from local breeder with same age broiler flocks and stored for 1 to 4 days prior to intimate other commercial ideal condition. All in and all out system was used in all incubation set, eggs were place 40 piece in tray from day one until day 17. Overall it was determined that the best setting temperature is 37°c 14day then 38°c 3day that can produce average 89.17% hatching, average first hatch is in the end of day 15 complete hatch in 16 day. Temperature set 38°c 14day, then 39°c3day is 84.17%, average first hatch is day 15.5 end 16 day, not harmful compared to 39°c14day, then 40°c3day with 76.67% hatching with average first hatch is day 15.5 end 16 day. With increasing setting temperature, up to 39°c to 40°c still not successful as 37°c to 38°c, excessive temperature did not affect hatchability neither drastically speed up the hatching days, but can cause detrimental effect, embryonic mortality to eggs development. First hatch in the end of day 14, average in day 15, complete hatching in the end of day 16 , this is faster than other incubator in the market that average 17 day/ cycle. This new faster cycle cause by the consistent heat flow and humidity inside incubation chamber surrounding the eggs shell. In conclusion, ideal setting temperature 37°c 14day 38°c 3day is the best setting temperature to incubate IKTA species quails, with the efficiency of machine supply consistence temperature, humidity and eggs movement are the main parameter to ensure high hatching rates of IKTA quails.